The MSCA Program: Developing Analytic Unicorns. Issue 1 (2nd January 2018) - Houghton, David M.; Schertzer, Clint; Beck, Scott
Abstract : Marketing analytics students who can communicate effectively with decision makers are in high demand. These "analytic unicorns" are hard to find. The Master of Science in Customer Analytics (MSCA) degree program at Xavier University seeks to fill that need. In this paper, we discuss the process of creating the MSCA program. We outline the program objectives and course requirements, and discuss the types of students we recruit. Finally, we introduce storytelling skills as a way to help marketing analytics students become analytic unicorns. Student learning outcomes (SLOs), methods of assessment, and learning exercises are included to aid in implementation.